Educação de Surdos: inclusão regular x escola bilíngue - NUNES, Maria de Fátima Gomes (Universidade Federal do Tocantins, 2023)
This article aims tounderstand the main events that occurred in bilingual education for the deaf today, and compare the impacts of Law no 14.191/2021 on the Law of Guidelines and Bases of National Education. It was after its enactment that a lot of things happened in this regard. Having as an important milestone the implementation of the Law of Guidelines and Bases of National Education, in force until the present day, as well as the determination of inclusive education. Another important milestone for the education of the deaf in Brazil was the recognition of the Brazilian Sign Language (Libras) by Law No. 10,436 of April 24, 2002, as the Official Language of the deaf community. Also Decree No. 5626 of December 22, 2005, which regulates the Libras Law and opens the way for bilingual education, the main claim of the deaf community. Therefore, it is believed to be extremely important to carry out further studies on this subject, which is so important for Brazilian deaf people.